Light spectrum impacts on development respiratory metabolism and antioxidant capacity of larval swimming crab Portunus trituberculatus - Zhang, Feifei; Zhang, Shuai; Ren, Zhiming; Song, Changbin; Ye, Yangfang; Mu, Changkao; Wang, Chunlin; Shi, Ce (Frontiers in Marine Science, 2022)
The effects of the spectrum on the development, respiratory metabolism, and antioxidant capacity of the larval swimming crab Portunus trituberculatus were studied. Seven light spectra, i.e., purple (400 nm), blue (425 nm), cyan (510 nm), green (525 nm), yellow (598 nm), red (638 nm), and white (full spectrum), were estimated. The larvae had the optimum survival rate and development under cyan light. On the contrary, larvae in red and yellow lights had poor growth performance. The oxygen consumption rate (OCR) dropped while the ammonia excretion rate (AER) rose as the larvae developed. Early larvae’s oxygen-nitrogen ratio (O: N) fell when exposed to red light, suggesting more protein was utilized in the respiratory process. Regarding the antioxidant system, crab had the lowest malondialdehyde (MDA) under green, cyan and yellow light, and the highest total antioxidant capacity (T-AOC) in cyan light. Taken together, the current results suggest that cyan was the optimum spectrum for the development of P. trituberculatus larvae.